Restored CD8+PD-1+ T Cells Facilitate the Response to Anti-PD-1 for Patients With Pancreatic Ductal Adenocarcinoma - Zhu, Qian; Qiao, Guoliang; Huang, Lefu; Xu, Chang; Guo, Deliang; Wang, Shuo; Zhao, Jing; Song, Yuguang; Liu, Bing; Chen, Zheng; Yang, Zhiyong; Yuan, Yufeng (Frontiers in Oncology, 2022)
Purpose We aimed to investigate the restoration of CD8+PD-1+ T cells through adoptive T-cell therapy (ACT) in relation to the prognosis and the therapeutic response to anti-PD-1 in patients with advanced pancreatic cancer (APC). Methods A total of 177 adult patients who underwent tumor resection as initial treatment for pancreatic ductal adenocarcinoma (PDAC) from February 2013 to July 2019 at Zhongnan Hospital of Wuhan University were enrolled in this study. Another cohort of 32 patients with APC was prospectively enrolled from Capital Medical University Cancer Center between June 1, 2013, and May 30, 2019. Results Of the 177 patients who received tumor resection, 67 tumor samples showed overexpression of PD-L1 and 110 patients with low expression of PD-L1. We found that overexpressed PD-L1 was a significant prognostic factor related to overall survival (OS). Furthermore, we tested the percentage of peripheral CD8+PD-1+ T cells in all patients and found that it was significantly correlated with the PD-L1 expression and the prognosis of patients with PDAC. The peripheral blood T lymphocyte subtypes were tracked for 30 months, and CD8+PD-1+ cells were shown to decrease. After that, we performed ACT for patients with APC in another cancer center. We found that the ratios of posttreatment of ACT/pre-ACT CD8+PD-1+ T cells were significantly related to the prognosis of patients with APC. Moreover, patients with combined treatment of ACT with anti-PD-1 had significantly favorable OS. Conclusions This study showed that the CD8+PD-1+ T-cell level was related to the expression of PD-L1. Restoring CD8+PD-1+ T cells in patients with APC by treatment of ACT significantly benefits the prognosis and facilitates the response to anti-PD-1.